Content Features of Medical Journal Zhong Xi Yi Xue Bao (《中西医学报》 The International Medical Journal) during the Republican Period and Its Impact on Medicine - Hai-Feng Cao; Li-Li Wang (Wolters Kluwer Health/LWW, 2021)
As a medical journal during the republican period, Zhong Xi Yi Xue Bao (《中西医学报》 The International Medical Journal) was characterized by rich and popular content, wide range of knowledge, and better popularization. It had played an important role in spreading modern Western medicine and popularizing medical knowledge in China, promoted the development of modern Chinese medicine and its integration with Western medicine, thus provided essential research value and far-reaching influence for medical science.